Effects of volcanic ash deposition on the early recovery of gap vegetation in Northwestern Patagonian steppes - Ghermandi, Luciana (2015)
Volcanic eruptions can cause changes in plant communities through the effects of ash fall. We studied the effect of ash deposition on vegetation recovery in inter-plant patches (gaps) following the eruption of the Puyehue-Cordón Caulle volcano (June 2011) in the Northwestern Patagonian steppe of Argentina. We estimated the aboveground vegetation cover and the seed bank abundance (April 2012) in gaps with and without ash (November 2011 and December 2012). We compared the sampled data with studies performed in the area before the eruption. Total plant cover was greater in gaps with ash compared to gaps without ash. Ash deposition suppressed cover of therophyte exotic species, but augmented total cover due to the increase of geophyte cover. Pre- and post-eruption soil seed bank was dominated by therophytes, mostly exotic species. However, ash deposition decreased the abundance of the total seed bank, including therophyte species. The position of buds and plant size in relation to ash layer thickness were important in determining plant recovery. Our results indicate that ash derived from volcanic activity can change species abundance and composition of steppe gaps that are important for the regeneration of matrix species.